Bilateral trade in the ASEAN transition economies: A gravity approach - Ismail, Normaz Wana; Smith, Peter (2007)
This study empirically investigates the effect of intra-regional trade in the ASEAN Transition Economies, namely Cambodia, Myanmar, Laos and Vietnam. Using the gravity model, this study examines whether the decision to join the ASEAN membership and the formation of the ASEAN Free Trade Area (AFTA) resulted in an increase in intra-regional trade for the period 1990 to 2005. From basic gravity variables, the study found that GDP as a proxy for market size, population, relative endowment, distance and common border are the main determinants of bilateral trade in the ASEAN Transition Economies. Overall results found that the intra imports decreased with the ASEAN Transition Economies but increased with the original ASEAN. Closer examination shows that Cambodia, Lao and Vietnam traded more with new members; meanwhile Myanmar imported more from the original ASEAN. This study also found that Vietnam increased exports more than imports to the original ASEAN.